Prevalence and determinants of eating disorder risk among Bangladeshi public university students: A cross-sectional study - Md​. Hasan Al Banna; Md​. Forshed Dewan; Mohammad Raihan Tariq; Abu Sayeed; Satyajit Kundu; Tasnim Rahman Disu; Sumaiya Akter; Sumaia Sahrin; Md Shafiqul Islam Khan (Health Psychology Research, 2021)
Eating disorders among university students have been increasing day by day in developing countries. However, there is a dearth of existing literature that assessed eating disorder risk among this population group in Bangladesh. Thus, this study aimed to assess the prevalence of eating disorder risk and its associated factors among university students. A cross-sectional study was conducted among 365 Bangladeshi public university students from October to December 2019. Data were collected by self-reported questionnaire on socio-demographic characteristics, risk of eating disorder, and nutritional status of study participants. The respondents’ eating disorder risk and nutritional status were assessed using the validated eating attitudes test-26 (EAT-26) tool and anthropometric measurement, respectively. A cut-off score of ≥ 20 based on EAT-26 indicates the presence of an eating disorder risk. Finally, a binary logistic regression was employed to identify the determinants of an eating disorder. The prevalence of ‘eating disorder risk’ was 23.0% (95% confidence interval [CI]: 18.6 to 27.4). Being female (adjusted odds ratio [AOR] = 2.4, 95% CI: 1.4 to 4.2), aged between 17-21 years (AOR = 2.0, 95% CI: 1.2 to 3.6), overweight (AOR = 4.9; 95% CI: 1.6 to 14.9) and obese (AOR = 7.7, 95% CI: 1.9 to 31.4) showed a higher odds of having an eating disorder risk in the present study. The higher prevalence of eating disorders in the study indicates that psychological intervention and health awareness programs, particularly to younger age, female, and overweight and obese students at the university level, would effectively prevent the eating disorder risk.